Oral mucosal manifestations of systemic disease. Issue 12 (December 2021) - Iles, Rebecca; Simms, Melanie; Ledsam, Alistair
Disorders spanning a wide range of body systems may, directly or indirectly, impact upon the orofacial tissues. Specifically, the oral mucosa may be the first, or most severely affected site of systemic disease, posing significant implications for oral health-related quality of life. It is not uncommon for patients to present to their GP with orofacial symptoms, therefore a firm understanding of how systemic disease can manifest in this way is important. This article will discuss oral mucosal presentations of systemic disease, aiming to improve understanding and recognition of these conditions, allowing appropriate referral for investigation, diagnosis and management.